Superiority of Preventive Antibiotic Treatment Compared with Standard Treatment of Poststroke Pneumonia in Experimental Stroke: A Bed to Bench Approach. Issue 6 (June 2013) - Hetze, Susann; Engel, Odilo; Römer, Christine; Mueller, Susanne; Dirnagl, Ulrich; Meisel, Christian; Meisel, Andreas
Stroke patients are prone to life-threatening bacterial pneumonia. Previous experimental stroke studies have demonstrated that preventive antibiotic treatment (PAT) improves outcome compared with placebo treatment, which however does not model the clinical setting properly. Here we investigate whether PAT is superior to the current clinical 'gold standard' for treating poststroke infections. Therefore, we modeled stroke care according to the current stroke guidelines recommending early antibiotic treatment after diagnosing infections. To reliably diagnose pneumonia in living mice, we established a general health score and a magnetic resonance imaging protocol for radiologic confirmation. Compared with standard treatment after diagnosis by these methods, PAT not only abolished pneumonia successfully but also improved general medical outcome. Both, preventive and standard antibiotic treatment using enrofloxacin improved survival in a similar way compared with placebo treatment. However, in contrast to standard treatment, only PAT improved functional outcome assessed by gait analysis. In conclusion, standard and preventive treatment approach reduced poststroke mortality, however at the cost of a worse neurologic outcome compared with preventive approach. These data support the concept of PAT for treating patients at risk for poststroke infections and warrant phase III trials to prove this concept in clinical setting.